The Influence of Macroeconomic Variables on The Indonesian Sharia Stock Index (ISSI) for The 2013-2019 Period - Nawindra, Indah; Wijayanto, Andhi (Universitas Negeri Semarang, 2020)
Investors believe that economic factors have a major impact on developments in the Islamic capital market. This study aims to describe and analyze macroeconomics of the Indonesian Sharia Stock Index (ISSI). The sample of this study consisted of 84 data consisting of all population data, namely all data on closing prices at the end of each month from exchange rates, BI Rate, inflation, world oil prices, world gold prices, and the Indonesian Sharia Stock Index (ISSI) for the period January 2013 - December. 2019. The analysis technique used is the Error Correction Model (ECM). The results showed that in the short term the exchange rate variable had a significant effect on the ISSI, while the BI Rate, inflation, world oil prices and world gold prices had no effect on the ISSI. In the long run, the variable exchange rate, BI Rate, inflation and world gold prices have a significant effect on the ISSI, while the world oil price variable has no effect on the ISSI